FEATURES AND PATTERNS OF MULTIFUNCTIONAL DEVELOPMENT OF AGRICULTURE - Kosenchuk, Olga; Sсryabina, Olga; Diner, Yuliya; Ryabkova, Dina (Revista Inclusiones, 2020)
This paper describes the features of the development of agricultural production and its functional ties with rural areas. They play an important role in providing food security of any country. The main purpose of this study is to identify the features and patterns of multifunctional development of agriculture on the example of Omsk region. It is a typical representative of Siberia. The paper makes a brief theoretical analysis of the development of agricultural production and rural areas by studying works of Russian and foreign authors. Most researchers connect the development of agriculture with the simultaneous development of villages. The others consider possible increase of efficiency in agriculture through the intensification of production and diversification of rural economy. The study identified positive and negative trends in the development of agricultural production and the functioning of rural areas.